Postoperative complications in patients infected with covid-19 (review of literature) - M. V. Timerbulatov; M. V. Zabelin; S. V. Timerbulatov; A. R. Gafarova; T. R. Nizamutdinov; V. M. Timerbulatov (Вестник хирургии имени И.И. Грекова, 2021)
The article provides an analysis of the literature on the frequency and nature of postoperative complications in patients infected with a new coronavirus infection – COVID-19. Risk factors for the development of postoperative complications and mortality are considered; the presence of SARS-CoV-2 is a leading risk factor for these complications and mortality, significant risk factors are also patients age ≥70 years, male gender, cancer surgery, severity of the patient’s condition before surgery (3–5 points on the ASA scale), performance emergency operations, a significant amount of surgical interventions. Postoperative complications in patients with COVID-19 develop in 50 %, the mortality rate is 2 times higher compared with patients without coronavirus infection.